Interactions of a prenylated flavonoid from Dalea elegans with fluconazole against azole- resistant Candida albicans - Barceló, Sebastián (2017)
Background The prenylated flavonoid 2′, 4′-dihydroxy-5′-(1′″, 1′″-dimethylallyl)-8-prenylpinocembrin (8PP, formerly 6PP) shows antifungal activity, inhibits rhodamine 6G efflux and reverses fluconazole (FCZ) resistance in azole-resistant Candida albicans overexpressing cdr1, cdr2 and mdr1 transporters. Purpose and design In this paper, we tried to characterize 8PP in vitro interactions on the cell growth and lethality of C. albicans. We also initiated preliminary in vivo toxicological studies on mice. Methods The effects of 8PP and FCZ on cell growth and viability of C. albicans were evaluated by CLSI guidelines. The checkerboard assay was used to search for interactions on cell growth. The time-kill assay was used to study fungicidal effects. Acute toxicity was evaluated at a single dose schedules. Results From the checkerboard design, and using a starting inoculum of 103 CFU/ml, the fractional inhibitory concentration (FIC) of FCZ and 8PP could be determined as 0.11 and 0.50, respectively, with a FIC index value (FICI) of 0.61. This FICI and the isobologram showing a concave shape suggests an additive interaction between them. At a higher starting inoculum (105 CFU/ml), C. albicans growth and viability were decreased by FCZ, 8PP and their combination in a concentration-dependent way. For FCZ, minimum fungicidal concentration (MFC) and FC50 (the concentration that kills 50% of the fungal cells) were 4-fold reduced (280–70 µM) in combination with 125 µM 8PP. A decrease of 3 log units in viable counts with respect to control was reached (3.65 ± 1.05 ‰, p < 0.0001). Thus, both fungistatic compounds when combined achieved an almost complete fungicidal effect at lower concentrations respecting of each of them alone. In preliminary toxicological assessment, lethal dose 50% (LD50) for 8PP by the i.p. route was 357 and 245 mg/kg, for female and male adult albino mice, respectively. FCZ LD50 was 785 and 650 mg/kg for female and male animals, respectively Conclusions In vitro results suggest additive interactions between 8PP and FCZ with respect to C. albicans cell growth. Besides killing per se, 8PP helps FCZ to achieve an almost complete fungicidal effect, which would be crucial to eradicate fungal infections.